Sex, Friends and Bullying Among Adolescents - Erni Gustina; Marsiana Wibowo (International Journal of Public Health Science (IJPHS), 2015)
Bullying is a common problem among adolescents in the world. Bullying gives serious long-term effects on mental and physical health. Several studies found that adolescent involvement in bullying was related with maladjustment for both male and female. Male are more involved in physical and verbal bullying, whereas girls are more involved in relational bullying. Having a lot of friends can protect adolescents from bullying behavior and reduce their vulnerability to be a bullying victim. The purpose of this study was to know the relationship between sex and the number of friends with bullying among adolescents in Junior high School at Yogyakarta city. This study was an observational analytic study with cross sectional design. The samples of the study were adolescent aged 13-15 years in five junior high schools. The instrument of the study was a questionnaire. Data were analyzed using chi square test. There were 250 adolescent involved in the study. The highest bullying incidence was 77.27% and the lowest was 22.73%. Both of them were verbal bullying. Bivariat analysis showed relationship was between sex and bullying (p= 0.03; PR= 0.74) and there was no relationship between the number of friends and bullying (p= 0.23; PR= 1.26). It can be concluded that there was relationship between sex and bullying among adolescents but there was no relationship between number of friends and bullying among adolescents. School should concern strict rules againt bullying behavior to minimize the occurrence of bullying behavior at school.